Senior High School Mathematics Teachers’ Perception of the Teaching and Learning of Logarithm in the Kwahu East District - Theophilus Klu Kwasi; Desire Sokpe; Justice Aggrey (Journal of Mathematics Instruction, Social Research and Opinion, 2024)
The motive of the study was to find factors that influence the teaching and learning of logarithms at the senior High schools in the Kwahu East Municipality. The study employed a descriptive survey where a questionnaire was administered to Eighty-Six (86) teachers. The sample was selected using the Census method. After the SPSS software was used to analyse the data, the descriptive analysis revealed that most teachers positively perceive logarithms. Factors influencing Senior High School mathematics teachers' teaching of logarithm were identified. Teachers believe that suitable teaching methods can influence students' perceptions. Strategies to encourage positive perceptions should be promoted among teachers, and recommendations include developing innovative methods for teaching logarithms in Senior High School mathematics.